Radiation tolerance of diamond detectors. Issue 1 (1st November 2022) - ,; Bäni, L; Artuso, M; Bachmair, F; Bartosik, M; Beck, H; Bellini, V; Belyaev, V; Bentele, B; Bergonzo, P; Bes, A; Brom, J-M; et al.
Abstract : Diamond is used as detector material in high energy physics experiments due to its inherent radiation tolerance. The RD42 collaboration has measured the radiation tolerance of chemical vapour deposition (CVD) diamond against proton, pion, and neutron irradiation. Results of this study are summarized in this article. The radiation tolerance of diamond detectors can be further enhanced by using a 3D electrode geometry. We present preliminary results of a poly-crystalline CVD (pCVD) diamond detector with a 3D electrode geometry after irradiation and compare to planar devices of roughly the same thickness.